Optimization of Cu/Sn Alloy Sputtering Process Based on Orthogonal Experimental Design Method - Shuangjie Liu; Xingwang Li; Yongping Hao; Xing Li; Fengli Liu (Micromachines, 2023)
The performance of supercapacitors is directly influenced by the conductivity of polypyrrole, which serves as the electrode material. In order to balance considerations of cost-effectiveness and conductivity, this study employs magnetron sputtering to fabricate a copper–tin alloy layer as the conductive layer for polypyrrole. The deposition of a copper–tin alloy film through magnetron sputtering has a significant impact on the polymerization effect of pyrrole as well as being a crucial factor influencing the performance of supercapacitors. Various parameters, including working pressure, sputtering time, and sputtering power, affect the conductivity of the copper–tin alloy film. Furthermore, the degree of influence of each parameter on the conductivity of the copper–tin alloy film varies. This study utilizes an orthogonal experimental design to investigate the impact of various factors and levels on the conductivity and uniformity of a metal film. The objective is to optimize the process parameters for the creation of a copper–tin alloy film with desirable characteristics. Experimental results indicate that the working voltage, sputtering time, and sputtering power significantly influence the coefficient of variation, deposition rate, target current, and operating voltage of the film. Furthermore, FT-IR, XRD, and SEM tests are conducted on samples prepared using the identified optimal process parameters. In addition, we demonstrate various approaches to enhance the experiment’s reliability. The findings indicate that the most favorable process parameters for achieving optimal results are a working pressure of 0.065 Pa, a sputtering time of 20 min, and a sputtering power of 70 W. It was observed that the sputtering time significantly influences the uniformity of the copper–tin alloy film, whereas the sputtering power has a minimal impact on its uniformity. The deposition rate is primarily influenced by the working pressure, with the greatest effect observed. Conversely, the sputtering time has the least impact on the deposition rate. Similarly, the target current is predominantly affected by the sputtering power, exhibiting the greatest influence, while the sputtering time has the least effect. Furthermore, the working voltage is most significantly influenced by the working pressure, whereas the sputtering time has the least impact on the working voltage.